Degradation of hazardous organic dyes with solar‐driven advanced oxidation process catalyzed by the mixed metal–organic frameworks. (15th April 2019) - Farrokhi, Alireza; Feizpour, Fahimeh; Asaadzadeh, Maryam
Abstract : phosphonate‐based bimetallic metal‐ organic frameworks, namely STA‐12(M1, M2 ) (M1, M2 = Mn, Fe, Co), show photocatalytic activity for the degradation of Rhodamine B (RhB) and Methylene blue (MB) from aqueous solution under natural sunlight irradiation. The degradation of the dyes, appears to be faster with STA‐12(Fe, Mn) than other synthesized MOFs. Thus, photo‐Fenton oxidative discoloration of dyes has been studied by H2 O2 catalyzed with the STA‐12(Fe, Mn). The process is first order with respect to dyes and the synergistic index in the STA‐12(Fe, Mn)/sunlight/H2 O2 system reached as high as 472%. Mineralization of dyes was discussed by spectroscopic and TOC measurement. Besides, the efficiency of STA‐12(Fe, Mn) used in photocatalytic process was attentively investigated through the characterization of reactive radicals, the stability and reusability of the photocatalyst, also the effect of operational parameters such as H2 O2 dosage, solution pH and initial dye concentration. This work demonstrates the first example of facilitating photo‐Fenton‐like excitation of H2 O2 via phosphonate based mixed metal organic frameworks as photocatalysts and explained a new opportunity for solar‐induced AOP environmental remediation and protection. Abstract : Phosphonate‐based bimetallic metal‐ organic frameworks, namely STA‐12(M1, M2 ) (M1, M2 = Mn, Fe, Co), show photocatalytic activity for the degradation of Rhodamine B (RhB) and Methylene blue (MB) from aqueous solution under natural sunlight irradiation.